(untitled) (Fractal: Journal of Psychology, 2010)
The article presents Freud’s conception of Science and the scientific enterprise using Freudian texts in which the author writes specifically about the scientific issue regarding psychoanalysis. To broaden the discussion, the german notions of Naturwissenchaft and Geistwissenchaft are introduced so as to shed light on the notions from which and with which Freud was dealing with. After this contextualization, Freud’s conception of science is confronted with the conceptions of Popper and Bachelard regarding science, as well as with other psychoanalysts ideas on this matter, such as Lacan and Kernberg, showing how their way of understanding science determines their position on the matter of Science and Psychoanalysis.